New Approach for Synthesis of Hexa (Allylamino) Cyclotriphosphazene Catalysed by an Ecologic and Friendly Catalyst Layered Called Maghnite-H+ (Algerian MMT). (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: 1H-NMR spectroscopy; dsc; nucleophilic substitution; cyclic structure; maghnite-h; phosphazene; hexa-allylamino-cyclotriphosphazene; allylamine; mald